EARLY SILURIAN SEA-LEVEL CHANGES - Loydell D.K. (My University, 1998)
Global sea-level fluctuated markedly during the early Silurian, probably as a result of the waxing and waning of ice-sheets in the South American portion of Gondwana. The highest sea-levels of the Silurian are recorded by the Telychian upper crispus–lower griestoniensis and spiralis–lower lapworthi biozones. Other highstands occurred in the early Aeronian, during the convolutus Zone (mid Aeronian), guerichi Zone and late turriculatus Zone (early Telychian), and early Sheinwoodian. Low sea-levels characterized much of the argenteus and sedgwickii zones (Aeronian), the utilis Subzone (late guerichi–early turriculatus zones, early Telychian), the late Telychian (commencing in the mid lapworthi Zone) and, after a period of apparently only small amplitude sea-level fluctuations in the late Sheinwoodian and earliest Homerian, the mid–late Homerian, in particular the early nassa Zone. Facies (and faunal) changes in the Lower Silurian do not support the P and S model of Jeppsson and others, but are consistent with the sea-level changes proposed herein. Mid Telychian marine red beds appear to have been deposited during a minor sea-level fall immediately after a period of very high sea-levels, rather than during a transgressive episode as previously suggested. Comparison of the sea-level curve presented herein with those constructed in the past is hampered by the lack of precision currently possible in the correlation of early Silurian deep water (graptolitic) and shallow water (shelly) sequences. Improving the precision of this correlation should be a priority for future research.
Keywords: Silurian; Paleozoic::Silurian; Палеозой::Силурийская